Organizational commitment and job satisfaction: Perspective of the Kedah State Treasury - Syed Mohd Ezman, Syed Zain (2016)
The purpose of this study is to examine the relationship between components of organizational commitment and job satisfaction among employee at Kedah State Treasury. Therefore this study could make important contribution to extant research in management and organizational behaviour. In the beginning of this study, the purpose, research question, and the need for the study is given. Then, literature is discussed about organizational commitment and job satisfaction that focusing on the relationship between them. There are 84 employees in population and the number of sample were 76 respondents. All data of the respective measurement items are tested with reliability and validity test based on Alpha Cronbach to the internal consistence by using SPSS program version 21. The result showed that affective, continuance and normative commitment have a significant positive relationship with job satisfaction.